The experiences of patients with advanced cancer and caregivers presenting to Emergency Departments: A qualitative study. (February 2018) - Philip, Jennifer; Remedios, Cheryl; Breen, Sibilah; Weiland, Tracey; Willenberg, Lisa; Boughey, Mark; Jelinek, George; Lane, Heather; Marck, Claudia; Weil, Jennifer
Background: Despite being a common event in the course of an advanced cancer illness, there is little understanding of patients' perceptions of hospital Emergency Department presentations. Aim: To explore the experiences and perceptions of Emergency Departments held by patients with advanced cancer and their informal caregivers. Design: Cross-sectional study involving semi-structured interviews with advanced cancer patients and their informal caregivers. Qualitative data analysis was underpinned by a phenomenological approach utilising a data-driven inductive thematic frame. Setting/participants: In total, 19 patients with advanced cancer who presented to Emergency Departments in the previous 6 months and 10 informal caregivers from an Australian public hospital and community palliative care service were interviewed. Results: Patients reported that Emergency Department presentations were largely prompted by worsening symptoms or were a means to expedite hospital admission, with many instructed to attend by their health care provider. The experience in the Emergency Department was described as a time of anxiety and uncertainty with concerns over communication, the general environment and delays in the symptom management highlighted. Long waits were common. Despite this, patients described relief at receiving care. While the Emergency Department was viewed as a safety net for the health system, many believed advanced cancer patients should have alternative options. Conclusion: Relatively simple changes of regular communication updates and early symptom relief would improve patient experience of Emergency Department care. However, since an Emergency Department presentation is frequently serving as a default to access medical care, a significant re-orientation of the health care system is required to meet patient needs.